2019
DOI: 10.1016/j.ast.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Skin friction drag reduction over staggered three dimensional cavities

Abstract: The effect of three-dimensional staggered circular cavities on a zero-pressure gradient incompressible turbulent boundary layer was studied. Two key parameters were varied, being the ratio of the diameter, d, to the depth, h, of the cavity, d/h and the Reynolds number based on the diameter of the cavity, R d. Velocity profile measurements showed that for the cases of d/h > 1 an increase in skin friction drag was experienced with respect to a smooth surface, but for d/h ≤ 1 the drag increment was almost negligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
4
22
0
Order By: Relevance
“…They reported drag-reduction margins of 3% for round axial-symmetrical dimples [Tay, 2011, Tay et al, 2015, 3.5% for round dimples where the lowest point of the non-axial-symmetric indentation was moved further downstream [Tay et al, 2016, Tay andLim, 2017], 6% for teardropshaped dimples [Tay and Lim, 2018], and 7.5% for diamond-shaped and elliptical dimples [Tay et al, 2019]. The recent experimental results on round dimples by Gowree et al [2019] confirmed the dragreduction results by Tay [2011], i.e., around 3%.…”
Section: Dimplesmentioning
confidence: 99%
“…They reported drag-reduction margins of 3% for round axial-symmetrical dimples [Tay, 2011, Tay et al, 2015, 3.5% for round dimples where the lowest point of the non-axial-symmetric indentation was moved further downstream [Tay et al, 2016, Tay andLim, 2017], 6% for teardropshaped dimples [Tay and Lim, 2018], and 7.5% for diamond-shaped and elliptical dimples [Tay et al, 2019]. The recent experimental results on round dimples by Gowree et al [2019] confirmed the dragreduction results by Tay [2011], i.e., around 3%.…”
Section: Dimplesmentioning
confidence: 99%
“…Recently, other studies addressed the possibility of having a skin friction reduction and an attenuation of sweep events by means of micro-cavity arrays (Gowree et al, 2019;Silvestri et al, 2017). In the work by Silvestri et al (2017), the reduction of the intensity of the sweep events is documented for certain values of the diameter scaled in wall units (20 < d þ < 145) with an optimum value that corresponds to d þ ¼ 60.…”
Section: Introductionmentioning
confidence: 99%
“…Because low-drag surfaces can be utilized in various fields such as automobiles, air crafts, ships, microfluidics, medical devices, and pipelines, shark skin inspired surfaces have been intensively researched for several decades. Despite the massive effort on this fascinating low-drag effect, not only mimicking but also even fabricating denticle-like structures is still a challenge with ordinary techniques due to the complexity of continuous hyperbolic curves and edges of the riblet geometry on the top of the denticles. Furthermore, although all denticles bring up drag-reduction based on similar principles, the morphological features such as the depth, shape, direction, and density of the riblets vary depending on the shark species and even on the part of a shark. , To date, most works on the fabrication of shark skin inspired low-drag surfaces can be categorized into (1) a simplified structure with a rectangular or triangular line pattern, (2) direct replication of a biological shark skin, and (3) 3D printing of biological shark skins. , While these attempts have successfully proved the mechanism and effectiveness of the structure on drag reduction, they do not provide systematic structural control and high flexibility in morphological change.…”
Section: Introductionmentioning
confidence: 99%